Analisis Bibliometrik Perkembangan Riset Media Pembelajaran Biologi Berbasis Teknologi di SMA Menggunakan Vosviewer: (Bibliometric Analysis of the Development of Technology-Based Biology Learning Media Research in High School Using Vosviewer) - Ihwan Fauzi Saputra; Bambang Hariyadi Bambang Hariyadi; Evita Anggereini Evita Anggereini (BIODIK, 2023)
The purpose of this study is to find out the development of research, the most productive researchers, research trends and research topics that have not been carried out. The source of the data in this study was obtained from the Google Scholar and Scopus websites. The data collection technique in this study used the Publish or Perish (PoP) application. Data analysis using bibliometric analysis assisted by Vosviewer. The results of bibliometric analysis produce 3 forms of data, namely Network Visualization showing the relationship between research topics, Overlay Visualization showing the renewal of a research and Density Visualization showing the number of research topics carried out. The results showed that the number of publications on technology-based biology learning media in high school in the period 2011-2021 always increased every year. The most productive researcher on technology-based Biology learning media is Ikhsan, J. who produced eight documents, Ichsan, Iz with seven documents. The topics of technology, development and learning are topics that are most often used together in Biology research articles or journals. The research topics that are the least carried out are on learning media in the form of applications, artificial intelligence, Augmented Reality and virtual environments. Key words: Bibliometrics, Media, Technology, Vosviewer Â  ABSTRAK Tujuan penelitian ini adalah untuk mengetahui perkembangan riset, peneliti paling produktif, tren penelitian dan topik penelitian yang belum dilakukan. Sumber data dalam penelitian ini yaitu diperoleh dari website Google Scholar dan Scopus. Teknik pengumpulan data pada penelitian ini menggunakan aplikasi Publish or Perish (PoP). Analisis data dengan menggunakan analisis bibliometrik berbantu Vosviewer. Hasil analisis bibliomterik menghasil 3 bentuk data yaitu Network Visualization menampilkan keterkaitan antar topik penelitian, Overlay Visualization menampilkan keterbaharuan sebuah penelitian dan Density Visualization menampilkan banyaknya topik penelitian yang dilakukan. Hasil penelitian didapatkan bahwa jumlah publikasi tentang media pembelajaran biologi berbasis teknologi di SMA pada rentang waktu tahun 2011-2021 setiap tahunnya selalu mengalami kenaikan. Peneliti paling produktif tentang media pembelajaran Biologi berbasis teknologi adalah Ikhsan, J. menghasilkan delapan dukumen, Ichsan, Iz dengan tujuh dokumen. Topik technology, development dan learning merupakan topik yang Â paling sering digunakan secara bersamaan dalam artikel atau jurnal penelitian Biologi. Topik penelitian yang paling sedikit dilakukan adalah tentang media pembelajaran dalam bentuk aplication, artificial intelegence, Augmented Reality dan virtual environment. Kata kunci: Bibliometrik, Media, Teknologi, Vosviewer